Theater art in the teaching of actions and analysis its interpretations - Professor Hamida Mahmudova (Zien Journals, 2023)
The main goal and task of pedagogical creative activity is to arm the future creators with the method of analysis of the work, which is the main tool of the director, depending on the personal civic position and worldview. And of course, it is to enrich practical activities with theoretical knowledge and build skills. Literacy, high skill of the director depends on knowing the analysis of behavior, developing skills for it, gaining experience and realizing it on the stage through the method of physical movement together with the actors (K.S. Stanislavsky "Method physical actions")
Keywords: Composite device; action-causing events; style of physical activity; behavior analysis